COMPUTER PROGRAMS FOR COMPARING DEPENDENT CORRELATIONS - Silver, N. Clayton (2016)
There are a variety of techniques for testing the differences between dependent correlations that are not available using the standard statistical software packages.  Examples of these techniques for examining different hypotheses within the dependent correlational realm are presented along with the output and interpretation from easily attainable, user-friendly, interactive software.